Assessment of the Impact of Fiscal Policy on the Current Account – the Twin Deficit Hypothesis in the Case of Macedonian Economy - Vesna Stojcevska; Mite Miteski (National Bank of the Republic of Macedonia, 2016)
For a small open economy with fixed exchange rate regime, the twin deficit hypothesis is always an interesting and relevant research topic. The aim of this research is to evaluate the effects of the government budget shocks on the current account movement in the case of the Macedonian economy, hoping to shed light on the influence of the fiscal policy on the external position of the economy, as well as to provide useful guidance for policy makers about the sensitivity of the current account balance to changes in the primary budget balance. By using a VAR model on quarterly data for the period from 1998 to 2013, this paper points to a positive relationship between the two balances, but the empirical results also indicate that connection is only contemporaneous, implying that fiscal policy stance does not cause long lasting changes in the balance of payments position of the Macedonian economy. However, our results do not undemand the need for fiscal cautiousness, especially in an economy with a fixed exchange rate regime.
Keywords: C32; E62; F31; F32; F41; 330; Government Budget Deficit; Balance of Goods and Services; Real Exchange Rate; Twin Deficit Hypothesis; VAR